Exploring environmental satisfaction in tourist sites: a view to Madeira Island - Mota, Luís (2020)
Characterizing tourism sustainability and studying environmental satisfaction in tourist sites, is part of a pilot study taking place in Madeira island. Tourism stakeholders and associations of relevant tourism services were interviewed to diagnose environmental issues arising from tourism activity and to identify tourist sites with priority in the study. Satisfaction was benchmarked in four tourist sites using individual attributes and overall fulfilment after experience on Madeira island. Sites ranged from two well-known walking routes in Rabaçal and Ribeiro Frio, representing a concern regarding conservation and visitation to the UNESCO site, the Laurisilva of Madeira; the viewpoint of Cape Girão with a skywalk positioned at 580m high, and the Santa Maria Street in Funchal, a popular street for eating-out, nightlife and street art paintings on entrance doors of the buildings. The experimental hypotheses assumed the same satisfaction level for all sites and by comparing Means of independent samples T-test, tourist sites were benchmarked for the study. Ribeiro Frio was pointed out as hotspot for tourism activity with many apprehensions, but statistics revealed the highest level of environmental satisfaction among visitors and tourists, followed by the viewpoint of Cabo Girão, Rabaçal and Santa Maria Street, and. Despite satisfaction being linked to the amount of people crowding an area, Ribeiro Frio was downgraded to the last position regarding on-site concentration of people. Such information is crucial for tourism planning and to assist further development. Parks, protected areas and tourist sites have attached an important perceived value, having managers interested in understanding visitors’ opinion in order to overcome challenges related to management, protection and conservation issues.